Protective effects of Peroxiredoxin 6 overexpression on amyloid β-induced apoptosis in PC12 cells. (October 2013) - Kim, I. K.; Lee, K. J.; Rhee, S.; Seo, S. B.; Pak, J. H.
Abstract Oxidative stress triggered by amyloid beta (Aβ) accumulation contributes substantially to the pathogenesis of Alzheimer's disease (AD). In the present study, we examined the involvement of the antioxidant activity of peroxiredoxin 6 (Prdx 6) in protecting against Aβ25–35-induced neurotoxicity in rat PC12 cells. Treatment of PC12 cells with Aβ25-35 resulted in a dose- and time-dependent cytotoxicity that was associated with increased accumulation of intracellular reactive oxygen species (ROS) and mitochondria-mediated apoptotic cell death, including activation of Caspase 3 and 9, inactivation of poly ADP-ribosyl polymerse (PARP), and dysregulation of Bcl-2 and Bax. This apoptotic signaling machinery was markedly attenuated in PC12 cells that overexpress wild-type Prdx 6, but not in cells that overexpress the C47S catalytic mutant of Prdx 6. This indicates that the peroxidase activity of Prdx 6 protects PC12 cells from Aβ25-35-induced neurotoxicity. The neuroprotective role of the antioxidant Prdx 6 suggests its therapeutic and/or prophylactic potential to slow the progression of AD and limit the extent of neuronal cell death caused by AD.